Moral Algorithms: Negotiating the Ethical Compass of Muslim Youth in the Digital Ecosystem - Ashfia Husna Fikroti Al-Ahya; Akhmad Affandi; Ahmad Yani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
Digital transformation has shifted the arena of value formation from physical spaces to algorithmically curated digital ecosystems. This study examines the role of social media algorithms in shaping the ethical compass of Muslim youth through a netnographic approach. The research aims to: (1) analyze the operational mechanisms of social media algorithms in shaping ethical discourse, (2) map the dynamics of value negotiation between Islamic teachings and global influences in digital spaces, and (3) formulate a digital ethics literacy model based on Islamic values. The study uses a qualitative approach with a netnographic design, involving in-depth interviews with 10 Muslim adolescents (15–23 years), content observation on Instagram, TikTok, YouTube, and Telegram over three months, and screen time analysis. Findings reveal an average social media usage of 4.2 hours per day, creating intensive exposure to algorithmic curation that forms a hybrid moral ecosystem. All participants experienced value conflicts and developed negotiation strategies through selective hybridization and the construction of hybrid religious authority. Most participants possessed basic algorithmic literacy, but its effectiveness was limited by system complexity. The study concludes that transformation of Islamic Religious Education is required through the integration of critical algorithmic literacy, strengthening of digital parenting, and multi-stakeholder collaboration so that Muslim youth can wisely navigate digital ecosystems based on Islamic values